ZEOLITE FOR AGRICULTURE INTENSIFICATION AND CATALYST IN AGROINDUSTRY - Kurniawan, Teguh; Nuryoto, Nuryoto; Firdaus, Mochamad Adha (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2019)
The role of renewable products is becoming important because the fossil resources in which most of our chemicals derived is vanishing. Agriculture as the renewable sources is needed to increase the production which is not only required to meet the food demands but also to replace chemicals that derived from fossil sources. Zeolite has a huge potential for agriculture intensification and conversion of agriculture products and by-products into chemicals. Indonesia has two kind deposit of natural zeolites, which are clinoptilolite and mordenite lies aligned volcanic mountain across Sumatra, Java, Nusa Tenggara and Sulawesi Islands. Zeolite has large surface area consisted of microporous and mesoporous structures. It could be utilized as an ion exchange agent, adsorbent and catalyst for applications in agriculture and agroindustry. Sustainable development of agricultural products could be also assisted by zeolite as slow-release fertilizer and controlling pests. Moreover, this review discusses about the integration of natural zeolite with chemical based wastes from livestock with nitrogen demand for cultivation is explained as a part of the idea of one-system-integrated farm and livestock. Storage and processing of agricultural products could be more efficient with the utilization of zeolite in drying, storage, processing and product preservation unit operations. Sucrose crystallization, catalytic reaction inulin to fructose, pinene isomerization and glycerol biodiesel by-product conversion is discussed in this review. As in general, zeolite porosity, topology, silicon to aluminium ratio, and acidity properties become an important factor on catalytic reactions to convert agricultural products into beneficial chemical substances